Revoluci ´on de los papeles: Una mirada desde la Revista de la Universidad Técnica del Estado (1969–1973) al proceso de la Reforma Universitaria en Chile. - Vásquez, Rita Torres (Latin American Research Review, 2022)
The Revista de la Universidad Técnica del Estado (1969–1973) was an academic periodical publication. Its aim was to disseminate the institution’s processes of transformation, which drew from the university reform movement. The periodical was immersed in the period of political transition, from the Christian democratic regime of Eduardo Frei Montalva to the socialist government programs of Salvador Allende. Its editorial production and printing processes were handled by the Universidad Técnica del Estado’s editorial department and graphic workshop, respectively—areas of the university whose work extended beyond institutional walls. This article aims to establish a dialogue between the publication and its political-educational context through reviewing a variety of topics, authors, and writing styles. Finally, it seeks to make visible the dynamics and experiences of the journal’s design work through analyzing visual production (covers and part-title pages) and the previously unpublished testimonials of the group of designers responsible for each issue.